Cardamonin inhibits the growth and stemness of osteosarcoma stem cells by inducing autophagy and inhibiting the Wnt/β-catenin signaling pathway - Lulu Zhang; Yu Jin; Qiannan Ding; Yulei Li; Lixia Yang; Mengyun Li; Zuo Lv; Kaifang Wang; Maowei Yang; Haixin Zhang; Xiucheng Li (Scientific Reports)
Abstract Cardamonin (CDN) has been shown to have promising anticancer effects against osteosarcoma (OS). Nevertheless, the molecular processes of it are still not well understood. Our investigation revealed that CDN has significant cytotoxic effects and diminishes cell viability in OS. The self-renewal ability was assessed using a sphere formation test, and the presence of marker proteins associated with cancer stem cells (CD133, SOX2, Nanog, and Oct4) was determined using Western blotting. These findings suggest that CDN significantly inhibits cancer stem cells (CSCs). Autophagy-related proteins (LC3, SQSTM1, Beclin1, and Atg5) were quantified via Western blotting, and the number of endogenous LC3 puncta was quantified via mRFP-GFP-LC3B adenovirus transfection. These outcomes manifest that CDN raises autophagy. The inhibition of autophagy with chloroquine (CQ) worsened the adverse effect of CDN on cancer stem cell stemness. This shows that CDN-induced autophagy inhibited the growth of osteosarcoma stem cells. The weakening of CSCs’ ability to maintain their stemness in OS is achieved by blocking the Wnt/β-catenin (WBC) signaling pathway via the action of CDN. Moreover, CDN induces autophagy, which has a negative regulatory effect on the WBC signaling pathway. Conversely, the WBC signaling pathway can also regulate autophagy induced by CDN. Ultimately, the antitumor activity of CDN was verified via in vivo experiments in an OS xenograft model. Immunohistochemical analysis revealed that CDN upregulated LC3 expression and decreased CD133 and β-catenin expression, aligned with the findings of the in vitro experiments. Overall, this study establishes an empirical basis for using CDN as a therapeutic medication that specifically targets CSCs in treating OS.